Developing TCP/IP and UDP traffic monitoring tool / Rafiq Che Mat - Che Mat, Rafiq (Faculty of Information Technology and Quantitative Sciences, 2005)
The main purpose of this project is to develop a program that uses Windows XP to monitor the flow of the Transmission Control Protocol / Internet Protocol (TCP/IP) and User Datagram Protocol (UDP) traffic over the Local Area Network (LAN) and internet. The purpose of the program is to monitor and track the record of TCP/IP and UDP cormection traffic, such as the amount of traffic being transmitted from or received by the host machine, based on different applications. For example, in the case of usage of file transfer, the TCP/IP and UDP Traffic monitor checks the details of the data transmission including the size of messages transmitted or received during a given period of time, the source IP address and MAC address, the destination IP address and MAC address, the source and destination port number, the type of protocol that have been used and etc. The monitoring will also have the ability to keep the tracked data in a database access file and provide some statistical information to the user such as a report, total number of TCP/IP and UDP protocol and etc. The last result is presented from the testing phase in this project.